Comissao das lagrimas, by Antonio Lobo Antunes: voices and (hyper)images against the silence of the world - Fonseca, Carlos Henrique [UNESP] (Univ Estadual Paulista-unesp, 2021)
In 2011, Antonio Lobo Antunes released his 23rd novel: Comissao das lagrimas. In this work, the tense relationship between Portugal and its former colonies opens space for one of the bloodiest episodes in the history of Angola after its independence in 1974: the performance of a special military court that ended up popularly known by the name that gives the title to this novel. This article aims to demonstrate how, in this novel, images, like photographs and their understanding in the construction of trauma, also understood as hyper images, almost always built in a lyrical way, fulfill the role of syntheses or indexes of violence. The use of images meets contemporary demands, related to the discursive conditions of the other, historically silenced.
Keywords: Antonio Lobo Antunes; Image; Hyper image; Trauma; Violence